2017
DOI: 10.1002/jcb.26206
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effect of ATP on In Vitro Mineralization of Dental Pulp Cells

Abstract: Dental pulp cells release adenosine triphosphate (ATP) in response to intrapulpal pressure and the amount released depends on the magnitude of the pressure. ATP regulates the differentiation of stem cells into adipocytes and osteoblasts. However, it is unknown whether extracellular ATP influences the stemness and osteogenic differentiation of stem cells from human exfoliated deciduous teeth (SHEDs). Therefore, this study investigated the effects of extracellular ATP at a low (0.1 mM) and high (10 mM) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Mechanistically, mechanical force stimulated ATP release via connexin43 and the intracellular calcium signaling pathway 26 . It has been reported that ATP supplementation in osteogenic medium enhanced osteogenic marker gene expression and mineralization in several cell types 27,[35][36][37] . In the present study, short-term ATP treatment prior to osteogenic induction did not influence osteogenic marker gene expression or mineralization by hPDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, mechanical force stimulated ATP release via connexin43 and the intracellular calcium signaling pathway 26 . It has been reported that ATP supplementation in osteogenic medium enhanced osteogenic marker gene expression and mineralization in several cell types 27,[35][36][37] . In the present study, short-term ATP treatment prior to osteogenic induction did not influence osteogenic marker gene expression or mineralization by hPDLs.…”
Section: Discussionmentioning
confidence: 99%
“…A mineralization assay was performed as described previously (Techatharatip, Nowwarote, Taebunpakul, & Pavasant, 2018). Cells were fixed with cold methanol for 10 min.…”
Section: In Vitro Mineralizationmentioning
confidence: 99%
“…ATP, which has been considered as an energy source, is also involved in the determination of cell fate, proliferation, metabolism, differentiation and apoptosis . Thereby, it is possible that ATP plays a vital role in promoting or preventing malignant transformation.…”
Section: Introductionmentioning
confidence: 99%